DURASI ( DUTA LITERASI ) UPAYA TINGKATKAN BUDAYA LITERASI WARGA SMPN 40 SURABAYA - eko Widayani (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2023)
The low level of literacy both nationally and in school culture requires schools to find solutions and innovations to drive a culture of literacy among students and the community. Therefore the principal must have an innovation program. One of the innovations raised is the Literacy Ambassador or DURASI, where this literacy ambassador will later help the school unit, namely the library, to increase literacy participation among students, especially SMPN 40 Surabaya. This Literacy Ambassador was taken because of the need for a literacy program that is able to increase student participation, therefore by involving students in one of the school programs so that the level of student participation increases. This program has the advantage of being close to students because students will be socialized and encouraged by their peers and support from the school so that this program will be very effective if implemented and aims to increase student participation in school literacy. The implementation of the DURASI program can increase the participation of students and school members where there are 3 published books made by school residents, students, and the School Committee. In addition, there are also collections of short stories made by students.